2018
DOI: 10.3390/molecules23112809
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide (H2S) Releasing Capacity of Isothiocyanates from Moringa oleifera Lam.

Abstract: Moringa oleifera Lam. is rich in phytochemical compounds especially glucosinolates (GSs) and isothiocyanates (ITCs), which are active compounds for cancer chemoprevention benefits of Brassicaceae vegetables. In this study, we determined the total contents of GSs and ITCs and their specific profiles in different Moringa tissues including seeds, stems, leaves and roots. Seeds (seeds with shell and seed kernel) showed significantly higher levels of total GSs and ITCs than that of other Moringa tissues. The hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 39 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…This has laid sound ground for researchers to understand the basis for pharmacological and nutraceutical properties of ITCs [ 126 ]. ITCs release H₂S by forming adduct with cysteine, then the adduct undergoes intramolecular cyclization with the liberation of either H₂S and dihydrothiazole derivatives or organic amine and raphanusamic acid [ 127 , 128 , 129 ]. In the study by Testai et al [ 130 ] the H₂S-donor 4-carboxyphenyl isothiocyanate protected against ischemia/reperfusion (I/R)-mediated myocardial tissue injury [ 130 ].…”
Section: Mechanism Of Cardio- and Neuroprotective Effectmentioning
confidence: 99%
“…This has laid sound ground for researchers to understand the basis for pharmacological and nutraceutical properties of ITCs [ 126 ]. ITCs release H₂S by forming adduct with cysteine, then the adduct undergoes intramolecular cyclization with the liberation of either H₂S and dihydrothiazole derivatives or organic amine and raphanusamic acid [ 127 , 128 , 129 ]. In the study by Testai et al [ 130 ] the H₂S-donor 4-carboxyphenyl isothiocyanate protected against ischemia/reperfusion (I/R)-mediated myocardial tissue injury [ 130 ].…”
Section: Mechanism Of Cardio- and Neuroprotective Effectmentioning
confidence: 99%
“…Recently the role of H2S release from glucosinolates/isothiocyanates as a potent mechanism of protective action in the cardiovascular compartment and in the nervous system has been reported [22], as well as the role of H2S-mediated pain-relieving effects of natural and synthetic isothiocyanates [23]. Due to the presence of the polar O-glycosylated phenol substituent, moringin is a solid, odorless and relatively stable compound at room temperature; these are uncommon features for most isothiocyanates obtained by crucifer plants, such as benzyl-and allylisothiocyanate from mustard which are usually small and volatile compounds, with a pungent smell.…”
Section: Moringa Oleifera Lam a Multi-purpose Treementioning
confidence: 99%
“…Recently the role of H 2 S release from glucosinolates/isothiocyanates as a potent mechanism of protective action in the cardiovascular compartment and in the nervous system has been reported [22], as well as the role of H 2 S-mediated pain-relieving effects of natural and synthetic isothiocyanates [23].…”
Section: Moringa Oleifera Lam a Multi-purpose Treementioning
confidence: 99%
“…In addition, H 2 S generated from 4-hydroxybenzyl ITC (HBITC), an ITC found in white mustard seeds (Sinapis alba), reportedly inhibits cellular proliferation of human neuroblastoma (SH-SY5Y) and glioblastoma (U87MG) cells (66). Wang et al showed H 2 S production in the tissue extracts of Moringa oleifera Lam; a species rich in GSLs and ITCs (179). Other studies indicate that subcutaneous and oral administrations of GRA or SFN reduced neuropathic pain in a dose-dependent manner in chemotherapy-induced neuropathy (91).…”
Section: Brassica Derived Sulfur Compoundsmentioning
confidence: 99%